2021
DOI: 10.3390/ijerph18083903
|View full text |Cite
|
Sign up to set email alerts
|

Personality of Public Health Organizations’ Instagram Accounts and According Differences in Photos at Content and Pixel Levels

Abstract: Organizations maintain social media accounts and upload posts to show their activities and communicate with the public, as individual users do. Thus, organizations’ social media accounts can be examined from the same perspective of that of individual users’ accounts, with personality being one of the perspectives. In line with previous studies that analyzed the personality of non-human objects such as products, stores, brands, and websites, this study analyzed the personality of Instagram accounts of public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…These results are distinct from the pattern in the personality of NPOs' Instagram accounts reported in this study. However, a similar pattern can be found in the personality of public health organizations' Instagram accounts (Kim and Lee, 2021): this suggest that Instagram accounts of public health organizations and NPOs share the similar personality in common. This result may be explained by the characteristics of those organizations: public health organizations and NPOs usually aim to contribute to the…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…These results are distinct from the pattern in the personality of NPOs' Instagram accounts reported in this study. However, a similar pattern can be found in the personality of public health organizations' Instagram accounts (Kim and Lee, 2021): this suggest that Instagram accounts of public health organizations and NPOs share the similar personality in common. This result may be explained by the characteristics of those organizations: public health organizations and NPOs usually aim to contribute to the…”
Section: Resultssupporting
confidence: 58%
“…However, the findings suggest that these two traits were visually manifested in an opposite manner. Previous studies have reported that openness and agreeableness were associated in opposite directions with SNS photo features (Liu, 2016;Segalin et al, 2017;Matz et al, 2019;Kim and Lee, 2021), but that was not the case with SNS text features (Pentina and Zhang, 2017;Miller, 2020). Thus, it can be possibly presumed that the difference between the two traits is amplified to be opposite to each other when visually represented in SNS photos.…”
Section: Correlations Between Personality Traits and Photo Features (...mentioning
confidence: 84%
See 1 more Smart Citation